(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
This contribution provides a synthesis of the palynological studies carried out on “Neocomian” units of the Golfo San Jorge Basin. Additionally, a revision of the palynological zones established for these units in previous works is presented, incorporating insights from new contributions and recent taxonomic novelties. Based on the palynological record, the age of the Las Heras Group is considered as not younger than Hauterivian at the northern and southern flanks of the Golfo San Jorge Basin. In contrast, the age of this group extends to the Aptian in the western area. Nevertheless, more detailed palynological studies and an evaluation of the current status of the stratigraphic units recognized in the analyzed wells are needed to confirm and expand these results.